Eclipsing Community? Neighborhood Disadvantage, Social Mechanisms, and Neighborly Attitudes and Behaviors. (September 2018) - Sharp, Gregory
This study investigates how objective neighborhood characteristics influence attitudinal and behavioral dimensions of community social organization. Grounded in ecological and neighborhood effects traditions, I extend prior inquiries by adjudicating the social mechanisms that link neighborhood disadvantage with residents' satisfaction and neighboring. Results from longitudinal data from the Los Angeles Family and Neighborhood Survey indicate that the neighborhood disadvantage perspective garners support when considering neighborhood satisfaction, while the systemic model marshals support for informal neighboring. Consistent with the local danger model, experiencing fearful feelings toward the neighborhood is detrimental to both satisfaction and neighboring. In addition, a cumulative disadvantage effect exists whereby individuals who live in highly disadvantaged areas and perceive the neighborhood as dangerous exhibit the highest levels of dissatisfaction. Having friendship ties living nearby buffers the impact of fear on neighborhood satisfaction, while being socially isolated exacerbates feelings of local danger. These findings suggest that community investment initiatives could mitigate the factors contributing to disadvantaged neighborhoods and foster local satisfaction and engagement as a result.